Outpatient single-port laparoscopic percutaneous Morgagni hernia repair assisted by an optical forceps. Issue 3 (4th May 2017) - Yilmaz, Engin; Afsarlar, Cagatay Evrim; Erdogan, Derya; Ozguner, Ismet Faruk
Abstract: Morgagni hernia is a relatively rare form of diaphragmatic hernia in the pediatric age group and it is conventionally treated with open surgical repair. Minimal access surgery is currently being adapted for many procedures in children. However, to date just a few techniques have been described relevant to minimal access surgical repair of Morgagni hernia in children. Herein, we report two cases of Morgagni hernia repaired by a new single-port laparoscopic technique assisted by an optical forceps. Two infants, a one-year-old boy and an eight-month-old girl, were operated with this technique in just 26 and 35 min and were discharged with oral analgesic prescription by postoperative hour 5 and 8, respectively. In the English-language literature, these cases are the first reports of laparoscopic Morgagni hernia repair that were performed as an outpatient procedure. Also, the technique introduced can be easily applied by a single surgeon without an assistant to operate the laparoscope.